Network Society: Digital Empowerment or Disempowerment - Ira Patriani; Hastin Trustisari; Sih Parmawati; Trinandari Prasetyo Nugrahanti; Tengku Kespandiar (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) Amuntai Kalimantan Selatan, 2023)
New skills and avenues for participation and self-expression in a connected society are made possible by ICT. Digital empowerment refers to the multi-step process of gaining access to better networking, communication, and collaboration opportunities and boosting the competency of individuals and communities so that they can play an influential role in society as a result of these developments. in the modern age of information. The goal of this essay is to investigate the relationship between inequality of participation and the degree to which individuals are empowered or disempowered in network society governance systems. A qualitative critical secondary data analysis was performed, in which published data and communication theory were used. This analysis contends that questions of the relationship between democracy and democratization and the role of computer-mediated communication in political communication are at the heart of the Digital Divide. The current Digital Gap is anticipated to add to structural disparities in political involvement as the role of ICT systems in political communication expands. As much as this inequality works against democracy and the political empowerment of some, it also creates chances for greater political participation by others. That raises questions about the social strata best positioned to profit from the coming networked society's electronic administration.